Quality of human milk expressed in a human milk bank and at home - Mayla S. Borges; Angela M. de M. Oliveira; Wallisen T. Hattori; Vânia O.S. Abdallah (Elsevier, 2018)
Objective: To evaluate the quality of the human milk expressed at home and at a human milk bank. Methods: This a retrospective, analytical, and observational study, performed by assessing titratable acidity records and the microbiological culture of 100 human milk samples expressed at home and at a human milk bank, in 2014. For the statistical analysis, generalized estimating equations (GEE) and the chi-squared test were used. Results: When comparing the two sample groups, no significant difference was found, with 98% and 94% of the samples being approved among those collected at the milk bank and at home, respectively. No main interaction effect between local and titratable acidity records (p = 0.285) was observed, and there was no statistically significant difference between the expected and observed values for the association between the collection place and the microbiological culture results (p = 0.307). Conclusions: The quality of human milk expressed at home and at the milk bank are in agreement with the recommended standards, confirming that the expression of human milk at home is as safe as expression at the human milk bank, provided that the established hygiene, conservation, storage, and transport standards are followed. Resumo: Objetivo: Avaliar a qualidade do leite humano ordenhado em domicílio e no Banco de Leite Humano. Métodos: Estudo retrospectivo, realizado por meio da avaliação dos registros da acidez titulável e dos resultados de cultura microbiológica de 100 amostras de leite humano ordenhado em domicílio e em um Banco de Leite Humano, no ano de 2014. Para análises estatísticas foram utilizadas as Equações de Estimação Generalizadas (Generalized Estimating Equations - GEE) e o teste Qui-quadrado. Resultados: Na comparação dos dois grupos de amostras, não foi detectada diferença significativa, sendo que 98% e 94% das amostras foram aprovadas entre as coletadas no Banco de Leite e em domicílio, respectivamente. Não foi observado efeito principal de interação entre local e grau de acidez titulável (p = 0,285) e não se constatou diferença estatisticamente significante entre os valores observados e esperados para associação entre local de coleta e o resultado da cultura microbiológica (p = 0,307). Conclusões: A qualidade do leite humano ordenhado em domicílio e no Banco de Leite Humano estão de acordo com o padrão preconizado, comprovando que a ordenha de leite humano em domicílio é tão segura quanto a ordenha no Banco de Leite Humano, desde que sejam seguidas as normas de higiene, conservação, armazenamento e transporte estabelecidas. Keywords: Human milk, Breast milk expression, Milk banks, Housing, Quality control, Palavras-chave: Leite humano, Extração de leite, Bancos de Leite, Habitação, Controle de qualidade